2017
DOI: 10.1007/s10096-017-3050-4
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of Pseudomonas aeruginosa and Stenotrophomonas maltophilia in hospitalised pneumonia patients has a synergic and significant impact on clinical outcomes

Abstract: Ventilator-acquired pneumonia and hospital community-acquired pneumonia are frequently caused by Gram-negative and -positive bacteria. We noted that pneumonia patients with co-infection of Pseudomonas aeruginosa and Stenotrophomonas maltophilia had a poor clinical outcome. To verify this, we retrospectively reviewed pneumonia cases at Hebei General Hospital from 2010 to 2015. These cases were grouped into four categories: (1) co-infection with P. aeruginosa and S. maltophilia, (2) infection with P. aeruginosa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 16 publications
3
26
0
3
Order By: Relevance
“…Taken together, our results, along with the experimental results on coinfection with parasites with different transmission strategies, target host tissues, virulence levels and different host specificity levels, suggest that interactions between phylogenetically distant parasitic organisms are mostly underlined by asymmetrical topdown mechanisms (Ben-Ami et al, 2011;Duncan et al, 2015;Fellous and Koella, 2009;Vojvodic et al, 2012;Yin et al, 2017; but see Graham, 2008, for a bottom-up example). This is in comparison to closely related parasites, which are more likely to interact through interference and bottom-up mechanisms (Hawlena et al, 2012;Ramiro et al, 2016;Wale et al, 2017).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Taken together, our results, along with the experimental results on coinfection with parasites with different transmission strategies, target host tissues, virulence levels and different host specificity levels, suggest that interactions between phylogenetically distant parasitic organisms are mostly underlined by asymmetrical topdown mechanisms (Ben-Ami et al, 2011;Duncan et al, 2015;Fellous and Koella, 2009;Vojvodic et al, 2012;Yin et al, 2017; but see Graham, 2008, for a bottom-up example). This is in comparison to closely related parasites, which are more likely to interact through interference and bottom-up mechanisms (Hawlena et al, 2012;Ramiro et al, 2016;Wale et al, 2017).…”
Section: Discussionsupporting
confidence: 63%
“…The latter mechanisms may be mediated by the host behavioral or immunological responses (Reviewed in Cox, 2001;Dianne et al, 2010;Mabbott, 2018;Supali et al, 2010) or through the damage caused to the host (e.g. Gleichsner et al, 2018;MĂ©ndez-Lozano et al, 2003;Yin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional methods identified only one Stenotrophomonas maltophilia sample compared to the multiplex PCR-based assay that identified it in five samples. Although Stenotrophomonas maltophilia is a gram-negative pathogen known to cause many severe infections and can result in mortality in approximately 14.6 to 42.5% of patients [26][27][28], pleural infection associated with this organism is rare [28]. Stenotrophomonas maltophilia is thought to cause nosocomial infections mainly in immunocompromised patients [28], but in our study, only one patient identified with this pathogen was immunocompromised and four of the five cases positive for Stenotrophomonas maltophilia had a final diagnosis of empyema.…”
Section: Discussionmentioning
confidence: 52%
“…We found that the multiplex PCR had a better sensitivity and specificity than conventional methods if the analysis is restricted to microorganisms included on the panel. Indeed, when using the clinical final diagnosis of empyema as a reference, the multiplex PCR-based assay had sensitivity six-times higher than that of the (34) No pathological finding 24 (33) Non-purulent secretion 23 (32) Erythema of the mucosa 20 (27) Purulent secretion 17 (23) Endobronchial tumour 8 (11) Bloody secretion 5 (7) conventional microbiologic methods. However, only a minority of the samples and a small percentage of the pathogens diagnosed by conventional methods were included in this panel including bacteria commonly involved in pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…6B), signifying that there is some specificity to the effect of the VirB/D4 T4SS. Since a role for the T4SS in interbacterial competition may be important in infected lungs, especially the CF lung, where multiple genera usually coexist (105)(106)(107), we coincubated our S. maltophilia strains with a P. aeruginosa strain. Wild-type K279a outcompeted P. aeruginosa strain 7700 (108,109) at all starting ratios, including 50, and even more importantly, the virB10 mutant defect was much more dramatic than it had been with the E. coli cocultures (Fig.…”
Section: Virb/d4 T4ss Enhances S Maltophilia Growth In the Presence mentioning
confidence: 99%